Artificial Intelligence Disruption in Public Relations: A Blessing or A Challenge? - Fifi Ee En Liew (Tecno Scientifica Publishing, 2021)
Artificial intelligence is bringing to the forefront of public relations functions new challenges as well as opportunity to achieve efficiency in communication with stakeholders. As shown in recent works, the acceptance and usage of artificial intelligence technologies by organization can help in measuring the return on investment of public relations efforts and ascertain congruency between organizational goals and objectives. This essay based on reflections and an interview with an experience public relations practitioner. The essay end by showing that artificial intelligence technology is here to stay. Therefore, public relations practitioners need to be adept of the technologies in order to increase the effectiveness of public relations functions.